2022
DOI: 10.1002/ima.22794
|View full text |Cite
|
Sign up to set email alerts
|

Medical image contrast enhancement based on improved sparrow search algorithm

Abstract: The collection or transmission of medical images is often disturbed by various factors, such as insufficient brightness and noise pollution, which will result in the deterioration of image quality and significantly affect the clinical diagnosis.To improve the quality of medical images, a contrast enhancement method based on improved sparrow search algorithm is proposed in this paper. The method is divided into two steps to enhance the medical images. First, a new transform function is introduced to improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…One avenue of research explores the enhancement of medical image segmentation through adaptive histogram equalization [50], highlighting its potential for contrast improvement [23,29,51]. Additionally, a comprehensive survey has delved into image enhancement techniques within medical imaging [52].…”
Section: Enhancement Techniquesmentioning
confidence: 99%
“…One avenue of research explores the enhancement of medical image segmentation through adaptive histogram equalization [50], highlighting its potential for contrast improvement [23,29,51]. Additionally, a comprehensive survey has delved into image enhancement techniques within medical imaging [52].…”
Section: Enhancement Techniquesmentioning
confidence: 99%
“…The SSA is an innovative heuristic optimization algorithm inspired by the foraging behavior of sparrows. The sparrows in the SSA are highly sensitive, exhaustive, and powerfully collaborative; these traits give the algorithm a strong search capability and optimization effect (Fan et al, 2022). The matrix in equation (1) illustrates its initial position:…”
Section: Ssamentioning
confidence: 99%
“…The SSA has been used in many other fields. Wu et al (2021) reported the application of GGSC-SSA to solve the traveling salesman problem (TSP); Fan et al (2022a) even utilized SSA to improve the quality of medical images; but few published reports exist on the application of SSA to UAV trajectory planning. Here we propose a new metaheuristic optimization algorithm based on the SSA and referred to as MSSA.…”
Section: Introductionmentioning
confidence: 99%